Gestión financiera en la Cooperativa de Transporte Urbano de Pasajeros “Santa Rita” de la ciudad de Babahoyo, durante el periodo 2022. - Jiménez Gaona, Magaly Julissa (2023)
At present, financial management is a key factor for the good performance of business activities, day by day companies expand globally, so it is of the utmost importance to ensure that they have control that allows efficient access to information. Maximizing its business value implies assuming the challenge of evaluating and adjusting processes in order to optimize the use of resources in order to obtain the expected results. Through proper financial management, the results faithful to the development of the company's activities can be obtained, which once the accounting process is completed will issue the results through the financial statements, which, being interpreted through financial analysis, issue the values that they allow the diagnosis of the real situation of the company and with it they facilitate a correct decision making. The present case study, when focusing on a fiscal period, was developed through vertical analysis, a financial analysis technique that includes the percentage weight of each element in the financial statements of a company in a certain period of time, with this it is intended to determine if the distribution of the company's assets and liabilities is the most suitable for its operational and financial needs.